Palm Tree Island - Strang, Herbert; Webb, Archibald, 1887-1944; Wright, Alan, 1864-1959? (Salt Lake City, UT : Project Gutenberg, 2011)
"Palm Tree Island" by Herbert Strang is a novel written in the early 20th century. It tells the adventurous tale of Harry Brent and his uncle, Stephen Brent, who embark on a seafaring journey filled with excitement, danger, and the exploration of new lands. The narrative revolves around Harry and his experiences as they are thrust into a world of maritime adventure, shipwreck, and survival after being stranded on a mysterious island in the Southern Hemisphere. At the start of the book, we are introduced to young Harry Brent, who reflects on his childhood and the influence of his adventurous uncle, Stephen. After years of living a quiet life in Stafford, Stephen's obsession with the sea leads him to plan a vast voyage that ultimately compels Harry to step into the adventurous life he dreams of. Throughout the opening chapters, an array of colorful characters are introduced, including sailors who share tales of the ocean, and we witness uncle Stephen's preparations for their expedition, which is packed with hopes of treasure and discovery. As the journey progresses, Harry's longing for adventure is set against the backdrop of familial relations and the unfolding challenges at sea, hinting at the tumultuous events that lie ahead. (This is an automatically generated summary.)
Release date is 2011-09-19
Produced by Al Haines
Keywords: Adventure stories; Shipwrecks -- Juvenile fiction; Castaways -- Juvenile fiction; Oceania -- Juvenile fiction